The peace dividend - Gleditsch, Nils Petter, 1942- (Elsevier, 1996)
The papers collected in this volume demonstrate how different kinds of analytical approach can be used to anticipate the economic repercussions of systematic reduction of military spending. This volume will be of interest to economists; scholars in peace studies, international relations and such like; and officials of national governments and international bodies dealing with disarmament issues and with economic restructuring.
Keywords: Disarmament -- Economic aspects -- Case studies.; Economic conversion -- Case studies.; Peace -- Economic aspects -- Case studies.; Defense industries -- Employees -- Supply and demand -- Case studies.; Unemployment -- Case studies.; elektronické knihy; electronic books